The spalt-related gene of Drosophila melanogaster is a member of an ancient gene family, defined by the adjacent, region-specific homeotic gene spalt. - Barrio, R.; Shea, M.J.; Carulli, J.; Lipkow, K.; Gaul, U.; Frommer, G.; Schuh, R.; Jackle, H.; Kafatos, F.C. (Development genes and evolution, 1996)
We report the full coding sequence of a new Drosophila gene, spalt-related, which is homologous and adjacent to the region-specific homeotic gene, spalt. Both genes have three widely spaced sets of C2H2 zinc finger motifs, but spalt-related encodes a fourth pair of C-terminal fingers resembling the Xenopus homologue, Xsal-1. The degrees of sequence divergence among all three members of this family are comparable, suggesting that the Drosophila genes originated from an ancient gene duplication. The spalt-related gene is expressed with quantitative variations from mid-embryogenesis (8-12?h) to the adult stage, but not in ovaries or early embryos. Expression is localized to limited parts of the body, including specific cell populations in the nervous system. In the wing disc, spalt and spalt-related are expressed in indistinguishable domains; in the nervous system and some other organs the expression patterns extensively overlap but are not identical, indicating that the genes have partially diverged in terms of developmental regulation. A characteristic central set of zinc fingers specifically binds to an A/T-rich consensus sequence, defining some DNA binding properties of this ancient family of nuclear factors.